2001
DOI: 10.1080/009083101316931906
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Aerogels for Oil-Spill Cleanup? Intrinsic Absorbing Properties

Abstract: A hydrophobic , CF 3 -functionalized silica aerogel has been applied to water-oil mixtures to determine oil absorbing capacity of the solid aerogel. Preliminary tests on Prudhoe Bay crude oil mixed with salt water, using the aerogel in powder form, show three regimes for absorbing based on oil to aerogel wt ratios ( O/A):1) all oil is absorbed and the aerogel is dry, O/A 0± 3.5; 2) all oil is involved in an oil± aerogel± water emulsion, O/A 4.6± 14; and 3) some oil is involved in an oil± aerogel± water emulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The unique morphological and interfacial properties make silica aerogels excellent adsorbents for various applications. Hrubesh et al [29] in 2001 modified silica aerogels with perfluoro functional groups such as CF 3 (trifluoromethyl) for adsorption of various organic solvents. Their results showed that the CF 3 -modified silica aerogels gain higher adsorption capacity for solvents than granular activated carbon (GAC).…”
Section: Silica Aerogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique morphological and interfacial properties make silica aerogels excellent adsorbents for various applications. Hrubesh et al [29] in 2001 modified silica aerogels with perfluoro functional groups such as CF 3 (trifluoromethyl) for adsorption of various organic solvents. Their results showed that the CF 3 -modified silica aerogels gain higher adsorption capacity for solvents than granular activated carbon (GAC).…”
Section: Silica Aerogelsmentioning
confidence: 99%
“…Their results showed that the CF 3 -modified silica aerogels gain higher adsorption capacity for solvents than granular activated carbon (GAC). Reynolds et al [29] compared the performances of CF 3 -modified aerogels with other absorbent materials previously developed. Their results indicated that CF 3 -modified aerogels in the non-powder form give better absorption capacity than in the powder form.…”
Section: Silica Aerogelsmentioning
confidence: 99%
“…Media Filtration (Resin, polymer, sand, clay, garnet, silica, walnut shell (Angelova et al, 2011;Blumenschein et al, 2001;C. Hank Rawlins, 2009;Franco et al, 2014;Reynolds et al, 2001;Srinivasan and Viraraghavan, 2008) viii. Membrane separation -micro-filtration (Hu and Scott, 2008;Motta et al, 2014); ultra-filtration Lipp et al, 1988;Weschenfelder et al, 2015); Nano-filtration (Mondal and Wickramasinghe, 2008;Xu and Drewes, 2006) and reverse osmosis (Al-Jeshi and Neville, 2008;Mohammadi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies highlighted their use in catalysis, which required high surface area and porosity [19,20]. After a lull of few decades, by early 2000s, intensive research toward the development of novel aerogels toward environmental cleanup [21,22], chemical sensors [23], filtering media [24] acoustic transducers [25], energy storage devices [26], metal casting molds [27], water repellant coatings [28], drug delivery and other biomedical and pharmaceutical applications [29], 30], extracting agents [31], and protective clothing [32].…”
Section: Introductionmentioning
confidence: 99%